Acute Brachial Artery Occlusion on Point-of-Care Ultrasound in the Emergency Department: A Case Report - Anisa Y. Mughal; Patrick Kishi (Clinical Practice and Cases in Emergency Medicine, 2022)
Introduction: This is a case report of an acute right brachial artery occlusion found on point-of-care ultrasound in the emergency department (ED) that illustrates the developing role of ultrasound in rapid differentiation and identification of acute vascular emergencies. Case Report: An 87-year-old male with a past medical history of coronary artery bypass graft presented to the ED with acute right upper extremity pain, with point-of-care ultrasound (POCUS) findings consistent with acute right brachial artery occlusion. Conclusion: Arterial occlusions are vascular emergencies that can be rapidly identified on POCUS.